2018
DOI: 10.1002/adem.201700782
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Nacre‐Like Ceramic with Nickel Inclusions Fabricated by Electroless Plating and Spark Plasma Sintering

Abstract: Hybrid composites of layered brittle-ductile constituents assembled in a brick-and-mortar architecture are promising for applications requiring high strength and toughness. Mostly, polymer mortars have been considered as the ductile layer in brick-and-mortar composites. However, low stiffness of polymers does not efficiently transfer the shear between hard ceramic bricks. Theoretical models point to metals as a more efficient mortar layer. However, infiltration of metals into ceramic scaffold is non-trivial, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…A) Comparison of reported mechanical properties of bioinspired (nacre‐like) alumina ceramics containing less than 10 vol% metallic mortar, taken from refs. (circular data points), with that of nacre (triangular data point) and the current results (square and diamond data points) to illustrate how the composition, processing, and sintering temperature can affect their damage‐tolerance (strength and toughness). B,C) Scanning electron microscopy image of the path of a crack in natural nacre and Ni+NiO‐coated alumina sintered at 1100 °C (with a 25 µm scale bar), shows toughening via the pull‐out of the platelets (with displacements in the range of a few micrometers) leading to crack bridging, the coarser‐scale defection of the crack path, roughly perpendicular to orientation of the platelets, and the corresponding formation of a rough fracture surface as the crack tried to maintain a macroscopic path nominally perpendicular to the applied tensile stress.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…A) Comparison of reported mechanical properties of bioinspired (nacre‐like) alumina ceramics containing less than 10 vol% metallic mortar, taken from refs. (circular data points), with that of nacre (triangular data point) and the current results (square and diamond data points) to illustrate how the composition, processing, and sintering temperature can affect their damage‐tolerance (strength and toughness). B,C) Scanning electron microscopy image of the path of a crack in natural nacre and Ni+NiO‐coated alumina sintered at 1100 °C (with a 25 µm scale bar), shows toughening via the pull‐out of the platelets (with displacements in the range of a few micrometers) leading to crack bridging, the coarser‐scale defection of the crack path, roughly perpendicular to orientation of the platelets, and the corresponding formation of a rough fracture surface as the crack tried to maintain a macroscopic path nominally perpendicular to the applied tensile stress.…”
mentioning
confidence: 83%
“…The mechanical properties of our Ni+NiO‐alumina ceramics have high damage‐tolerance relative to other bioinspired ceramics with a <10 vol% metallic phase (Figure a). For example, a similar approach was used in a previous study, but the reported toughness values were an order of magnitude lower than the ceramics developed here, which may have originated from poor bonding between the ceramic and metallic phases (NiO‐coatings were not employed). Slip‐casting or freeze‐casting has also been used to process alumina/copper and alumina/nickel materials, and freeze‐casting has been employed to align Ni‐coated alumina platelets prior to hot pressing, but in all these cases the resulting toughnesses were significantly lower than the materials developed here, we presume due to extensive dewetting of the metallic phase.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…To describe the evolution of the crack extension length and crack growth resistance during crack propagation, the crack growth resistance curve (R‐curve) is usually calculated from a J‐integral by accounting for the local deflection and other dissipation mechanisms. This approach reflects the relationship between the fracture growth toughness ( K JC ) and crack extension length (Δ a ) extracted from the load‐displacement curves . Details on the R‐curve calculation are explained below.…”
Section: Resultsmentioning
confidence: 99%
“…This approach reflects the relationship between the fracture growth toughness (K JC ) and crack extension length (Δa) extracted from the load-displacement curves. 30,31 Details on the R-curve calculation are explained below.…”
Section: Fracture-resistant Behavior Of Fibrous Monolithic Ceramicsmentioning
confidence: 99%